Method for preparing 4N8-grade high-purity quartz sand through high-pressure roller milling flotation of pegmatite
Through the processes of color sorting, high-pressure roller grinding, magnetic sorting and three-flotation, the problems of dust, noise, low sand yield and high pollution in traditional crushing and flotation processes are solved, and the 4N8-level high-purity quartz sand is efficiently and environmentally friendly.
Patent Information
- Application Number
- CN202510218902.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-26
- Publication Date
- 2025-04-22
AI Technical Summary
Existing jaw crushers and roller sands produce a lot of dust and noise, the sand yield is low, the raw material utilization rate is low, and the traditional flotation process can only initially remove impurities from minerals, and processes such as acid leaching and chlorination are required to purify the high-purity quartz sand required for semiconductor products.
The raw materials are initially screened by a color sorter, and the quartz sand is crushed through a high-pressure roller mill. Combined with magnetic separation and three-flotation processes, mica, feldspar and metal impurities are removed to obtain 4N8-level high-purity quartz sand.
It significantly improves the purity of quartz raw materials and sand making efficiency, reduces dust generation, avoids pollution processes such as acid leaching and chlorination, and improves raw material utilization and economic benefits.
Smart Images

Figure CN119857577A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of quartz purification technology, and in particular to a method for preparing 4N8 grade high-purity quartz sand by high-pressure roller mill flotation of pegmatite. Background Art
[0002] The SiO2 content in high-purity quartz sand is ≥99.998%. It has excellent properties such as high temperature resistance, corrosion resistance, and high insulation. It is widely used in semiconductors, photovoltaics, new energy, and military industries. Only high-quality primary crystals and secondary crystals in nature can meet the requirements. my country's high-quality crystal resources are limited, and the rapid development of industries such as optical fiber communications, semiconductors, and photovoltaics has led to the depletion of raw materials for the preparation of high-purity quartz. Therefore, the use of various sorting methods to sort and prepare high-purity quartz sand from quartz resources has become a research focus.
[0003] In order to meet the high purity requirements of quartz sand, the current purification process is rather cumbersome, including crushing, screening, magnetic separation, flotation, acid leaching, chlorination roasting, etc., which usually requires multiple methods to work together, and sometimes a single process is repeated multiple times.
[0004] At present, the traditional sand making method mainly uses mechanical crushing equipment, such as jaw crusher, whose jaw plate performs preliminary crushing of ore by squeezing, splitting, impacting, etc. However, this method has a large loss of raw materials during the crushing process and can only crush it into larger particles. In order to further crush these particles, it is usually necessary to use a roller mill to crush the ore for the second time. Since traditional mechanical crushing equipment requires multiple stages during the working process, the whole process is complicated and time-consuming, resulting in low sand making efficiency, especially the use of jaw crusher and roller mill, which often produces a lot of dust and noise. In addition, its sand yield is relatively low, and a large amount of ore is not converted into qualified particle size sand, thereby reducing the raw material utilization rate and affecting the overall economic benefits. With the development of crushing technology, the application of high-pressure roller mill is increasing. For example, patents CN202411063443.5, CN202421704956.5, CN 116654944 A, CN201910922282.3, etc. use high-pressure roller mills for the crushing of minerals such as magnetite and ceramic raw materials. Compared with traditional methods, high pressure roller mills are more efficient, greatly shorten the production cycle, and reduce the energy consumption and maintenance costs of equipment. In addition, the use of high pressure roller mills to make sand has a higher sand yield, which can effectively separate the target ore from the gangue, avoiding the common resource waste problem in traditional machinery, helping to maintain the continuity of the grinding process, and improve production efficiency. It can also obtain fine-grained products with more uniform particle size. Therefore, with the emphasis on production efficiency, environmental protection and resource utilization, the application of high pressure roller mills has become an important trend in modern ore crushing and sand making processes. More and more mining companies have begun to use high pressure roller mills to replace traditional crushing and grinding machinery and equipment. For example, patents CN116654944 A and CN201910922282.3 both use high-pressure roller mills for the preparation of quartz sand raw materials. Patent CN201910922282.3 discloses a dry powder making method for coarse-grained granite pegmatite sorting. After crushing by the high-pressure roller mill, it is necessary to use a hammer crusher to grind to the target particle size; patent CN 116654944 A discloses a green and efficient method for preparing high-purity quartz, which uses a high-pressure roller mill to dissociate the quartz raw material. However, before crushing, the raw material needs to be pre-treated by "roasting-water quenching" at 800-900°C for 0.5-1h, and acid leaching is required to prepare the high-purity quartz sand raw material. Although the method disclosed in the patent can efficiently prepare high-purity quartz sand above grade 4N8, it has many preparation steps, and the acid leaching operation usually consumes a large amount of hydrochloric acid, nitric acid and hydrofluoric acid, which pollutes the environment.
[0005] On the other hand, flotation is a separation method based on the difference in hydrophilicity and hydrophobicity of the particle surface, which causes the target mineral to float or sink with bubbles. This process requires the addition of surfactants, stirring and aeration devices to cooperate with each other to achieve the purpose of sorting. The selection of reagents and the degree of operation standardization are the key to achieving efficient separation of quartz sand and gangue. At present, traditional methods can only remove a small amount of impurity minerals such as feldspar and mica, and other methods are required for subsequent purification operations, such as acid leaching and chlorination roasting. In acid leaching operations, the leachate usually consumes a large amount of acid, such as hydrochloric acid and hydrofluoric acid, which will produce irritating and highly corrosive volatile gases at high temperatures, and long-term contact is carcinogenic; the waste gas generated during chlorination roasting contains harmful substances such as chlorine and hydrogen chloride, which are highly corrosive. Its recovery and treatment require a lot of money and equipment, increasing operating costs. In addition, chlorination roasting usually needs to be carried out under high temperature conditions, consumes a lot of energy, and has high requirements on the material, structure and sealing performance of the equipment. Summary of the invention
[0006] In view of the technical problems existing in the background technology, the present application provides a method for preparing 4N8 grade high-purity quartz sand by high-pressure roller mill flotation of pegmatite, aiming to solve the problems of large amount of dust and noise generated by existing jaw crushers and double roller machines when making sand, low sand yield, low raw material utilization rate, etc. The traditional flotation process can only preliminarily remove impurities in minerals, and the flotation products must undergo acid leaching, chlorination roasting and other processes to purify the quartz sand to the raw material requirements required for semiconductor products.
[0007] In a first aspect, the present application provides a method for preparing 4N8 grade high-purity quartz sand by high-pressure roller mill flotation of pegmatite, comprising the following steps: S1. Using a color sorter to screen the raw ore, remove the miscellaneous gangue minerals, and obtain the first quartz sand raw material; S2, crushing the first quartz sand raw material into fine sand, and then screening and magnetically separating to obtain a second quartz sand raw material; S3, mixing the second quartz sand raw material with water to form a slurry, and then flotation three times in sequence, and obtaining a high-purity quartz sand product after drug removal and material discharge; The step S3 specifically includes the following steps: adding a first collector to the ore pulp for a first flotation to remove mica and obtain a first flotation tailing, wherein the first collector is an amine collector; adding a second collector to the first flotation tailing for a second flotation to remove feldspar and obtain a second flotation tailing, wherein the second collector is an anionic organic surfactant; adding a third collector to the second flotation tailing for a third flotation to remove metal impurities and obtain a third flotation tailing, wherein the third collector is a fatty acid organic surfactant.
[0008] In some embodiments, in step S2, the first quartz sand raw material is crushed by a high pressure roller mill, the pressure of the high pressure roller mill is ≤20 MPa, the feed particle size is ≤30 mm, and the throughput is 200~400 t / h.
[0009] In some embodiments, the particle size of the fine sand is 60-160 mesh.
[0010] In some embodiments, in step S3, the pulp concentration in the first flotation is 25-45%, the temperature is 35-60°C, and the pH is adjusted to 2-4 by a pH adjuster; the temperature in the second flotation is 35-60°C, and the pH is adjusted to 2-4 by a pH adjuster; the temperature in the third flotation is 35-60°C, and the pH is adjusted to 5-8 by a pH adjuster.
[0011] In some embodiments, the pH adjuster is one or more of sulfuric acid, hydrochloric acid, nitric acid, and sodium hydroxide.
[0012] In some embodiments, the stirring speed during flotation is 200-600 r / min, and the aeration volume is 0.8-1.5 m 3 / min.
[0013] In some embodiments, the first flotation is repeated multiple times until there are no visible gangue mineral particles in the foam layer of the first flotation, and the first collector is used in an amount of 10-80 g / t each time, and the first collector includes one or more of dodecylamine, tetradecylamine, hexadecylamine, octadecylamine, and etheramine.
[0014] In some embodiments, the second flotation is repeated multiple times until there are no visible gangue mineral particles in the foam layer of the second flotation, and the second collector is used in an amount of 10-80 g / t each time, and the second collector includes one or more of sodium petroleum sulfonate, sodium dodecyl sulfate, and sodium oleate.
[0015] In some embodiments, the third flotation is repeated multiple times until there are no visible gangue mineral particles in the foam layer of the third flotation, and the third collector is used in an amount of 5 to 50 g / t each time, and the third collector includes one or more of myristic acid, palmitic acid, rapeseed acid, linoleic acid, and linolenic acid.
[0016] In some embodiments, the drug removal and discharge step in step S4 includes: adding water, gas and stirring to the third flotation tailings to perform drug removal operations, stirring for 30 to 40 minutes, draining, circulating 2 to 3 times, and draining after drug removal is completed.
[0017] Different from the existing technical solutions, the beneficial effects of this application include: 1. This application uses a color sorter to pre-screen the raw materials. Through the color difference of the particle surface, it can quickly remove visible impurities, especially feldspar, mica, iron-containing and other common colored impurity minerals, which can significantly improve the purity of quartz raw materials. A high-field strength dry magnetic separator is used to remove magnetic gangue minerals in quartz sand. A high-pressure roller mill is used to make sand from blocky quartz, which can efficiently crush large blocks into fine sand and has a significant monomer dissociation effect. This efficient crushing method can effectively destroy the binding force between particles, and the separation between quartz and impurity mineral particles is significantly improved, creating favorable conditions for subsequent flotation and improving sand making efficiency.
[0018] 2. This application has developed a new flotation impurity removal system, which removes mica in the first flotation, feldspar in the second flotation, and metal minerals in the third flotation. This flotation process can efficiently remove common associated impurity minerals. This application adopts color sorting-high-pressure roller grinding sand making-magnetic separation-flotation process, which has fewer operating steps, no acid leaching, no fluorine and no nitrate, and can reduce environmental pollution. This process is simple and efficient, has high economy and environmental protection, is suitable for large-scale quartz sand production and purification, and has broad application prospects.
[0019] 3. Simple operation. The purification process only includes color sorting - high-pressure roller grinding - magnetic separation - flotation. There is no acid leaching operation, which greatly reduces the operation risk and reduces environmental pollution.
[0020] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0022] Figure 1 This is a process flow chart of an embodiment of the present application. DETAILED DESCRIPTION
[0023] The following embodiments of the technical solution of the present application will be described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and therefore, are only used as examples and cannot be used to limit the scope of protection of the present application.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field of this application; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0025] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two), similarly, "multiple groups" refers to more than two (including two groups), and "multiple pieces" refers to more than two (including two pieces).
[0026] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0027] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0028] Since traditional mechanical crushing equipment requires multiple stages in the working process, the whole process is complicated and time-consuming, resulting in low sand making efficiency, especially the use of jaw crushers and roller crushers, which often generate a lot of dust and noise. In addition, its sand yield is relatively low, and a large amount of ore is not converted into qualified sand particles, which reduces the utilization rate of raw materials and affects the overall economic benefits. On the other hand, flotation is a separation method based on the difference in hydrophilicity and hydrophobicity of the particle surface, so that the target mineral floats or sinks with bubbles. This process requires the addition of surfactants, stirring and aeration devices to cooperate with each other to achieve the purpose of sorting. The selection of reagents and the degree of operation standardization are the key to achieving efficient separation of quartz sand and gangue. At present, the traditional method can only achieve preliminary removal. The impurity content in the floated product is usually very high. Acid leaching, chlorination roasting and other processes must be carried out to purify quartz to the raw material requirements of high-purity quartz sand required for semiconductors and photovoltaic products.
[0029] In order to solve the problems that the existing jaw crusher and roller machine will generate a lot of dust and noise when making sand, and the sand yield is low, the raw material utilization rate is low, etc., the traditional flotation process can only preliminarily remove impurities in the minerals, and the product after flotation must be subjected to acid leaching, chlorination roasting and other processes to purify the quartz into high-purity quartz sand raw materials required for semiconductor products. The present application provides a method for preparing 4N8 grade high-purity quartz sand by flotation of pegmatite high-pressure roller mill, wherein a color sorter is used to perform preliminary screening of the raw materials, and the visible impurities, especially feldspar, mica, iron-containing and other common colored impurity minerals, can be quickly removed by the difference in color of the particle surface, thereby significantly improving the purity of the quartz raw materials, a high-field strength dry magnetic separator is used to remove the magnetic gangue minerals in the quartz sand, and a high-pressure roller mill is used to make sand for the blocky quartz, which can be efficiently crushed into fine sand and has a significant monomer dissociation effect, creating favorable conditions for subsequent flotation, not only improving the sand making efficiency, but also greatly reducing dust generation and protecting the health of workers.
[0030] like Figure 1 As shown, the embodiment of the present application provides a method for preparing 4N8 grade high-purity quartz sand by high-pressure roller mill flotation of pegmatite, comprising the following steps: S1. Color sorting the raw ore to remove the miscellaneous gangue minerals to obtain the first quartz sand raw material; S2, crushing the first quartz sand raw material into fine sand, and then screening and magnetically separating to obtain a second quartz sand raw material; S3, mixing the second quartz sand raw material with water to form a slurry, and then flotation three times in sequence, and obtaining a high-purity quartz sand product after drug removal and material discharge; The step S3 specifically includes the following steps: adding a first collector to the ore pulp for a first flotation to remove mica and obtain a first flotation tailing, wherein the first collector is an amine collector; adding a second collector to the first flotation tailing for a second flotation to remove feldspar and obtain a second flotation tailing, wherein the second collector is an anionic organic surfactant; adding a third collector to the second flotation tailing for a third flotation to remove metal impurities and obtain a third flotation tailing, wherein the third collector is a fatty acid organic surfactant.
[0031] In the technical solution of the embodiment of the present application, a color sorter is preferably used for preliminary screening. Based on the distribution characteristics between quartz and gangue observed under a microscope, a suitable color mode RGB mode or HSL mode is set; the setting is made according to the color of impurities in the product. For example, gray, black, red and other impurities need to be removed from pegmatite, and only white and transparent particles are retained; a suitable area threshold is set according to the impurity area of the sample, so that large pieces of feldspar, quartz and other colorful gangue minerals can be removed.
[0032] The screened first quartz sand raw material is prepared into fine sand through a high-pressure roller mill, and the second quartz sand raw material with a particle size of 60-160 mesh is obtained by screening. When using the high-pressure roller mill, the pressure of the equipment is adjusted, and the large pieces of the second quartz sand raw material are selectively broken along the quartz and gangue grain boundaries under high pressure conditions, which is conducive to the dissociation of monomers between different minerals.
[0033] A dry magnetic separator is used for magnetic separation and purification. The second quartz sand raw material screened in step S2 is fed into the magnetic separator, and an appropriate magnetic field strength (4000 ~ 8000 Gs) is selected to remove the magnetic gangue in the ore. Through rotation and magnetic field action, magnetic ores (such as magnetite, hematite, etc.) will be adsorbed, while non-magnetic ores (such as quartz) will be separated out.
[0034] The second quartz sand raw material is mixed with water to form a slurry and then flotation is performed. The first step is to remove mica, the second step is to remove feldspar, and the third step is to remove metal elements. This process can efficiently remove common associated impurities. The order of the first flotation and the second flotation in this application can be reversed. The first collector and the second collector promote the flotation of mica and feldspar through various means such as charge interaction, surface hydrophobicity change, and ion exchange, thereby achieving the purpose of effective separation. The third collector is a fatty acid organic surfactant, which removes metal gangue minerals in the ore by combining with metal impurities, usually including metal ores containing copper, zinc, iron, etc., and reacts physically and chemically with metal ions. It can make the metal ores hydrophobic through complexation or adsorption with metal ions, thereby being separated out and reducing its content in the final high-purity quartz sand product.
[0035] In order to avoid the interaction between reagents at different stages, a de-drug operation is required after each flotation operation to remove the reagents added in the last flotation.
[0036] In some embodiments, in step S2, the first quartz sand raw material is crushed by a high pressure roller mill, the pressure of the high pressure roller mill is ≤20 MPa, the feed particle size is ≤30 mm, and the throughput is 200~400 t / h.
[0037] In some embodiments, the particle size of the fine sand is 60-160 mesh.
[0038] In the technical solution of the embodiment of the present application, a high-pressure roller mill is used. Compared with the traditional impact crushing method, the high-pressure roller mill is more efficient and can be directly converted into fine-grained materials, saving about 30% of energy consumption. It has high crushing efficiency and greatly shortens the production cycle. It not only reduces the energy consumption and maintenance cost of the equipment, but also has a high sand yield. In addition, the high-pressure roller mill can generate different pressures according to the different characteristics of the material, and the hydraulic cylinder can move the adjustment roller along the guide groove during the pressure application process; and the high-pressure roller mill realizes the crushing process through two rollers rotating in opposite directions, one of which is fixed and the other can be moved. The material is fed from above the two rollers, and after being subjected to high pressure, it becomes a dense cake and is discharged from the bottom of the machine. Under the high pressure of the high-pressure roller mill, the quartz raw material breaks along the grain boundaries of quartz and gangue, which is conducive to the dissociation of monomers between different minerals, and can remove the fluid inclusions in the particles to a certain extent. It can also obtain products with more uniform particle size, meeting the market demand for quartz sand particle size.
[0039] In some embodiments, in step S3, the pulp concentration in the first flotation is 25-45%, the temperature is 35-60°C, and the pH is adjusted to 2-4 by a pH adjuster; the temperature in the second flotation is 35-60°C, and the pH is adjusted to 2-4 by a pH adjuster; the temperature in the third flotation is 35-60°C, and the pH is adjusted to 5-8 by a pH adjuster.
[0040] In some embodiments, the pH adjuster is one or more of sulfuric acid, hydrochloric acid, nitric acid, and sodium hydroxide.
[0041] In some embodiments, the stirring speed during flotation is 200-600 r / min, and the aeration volume is 0.8-1.5 m 3 / min.
[0042] In some embodiments, the first flotation is repeated multiple times until there is no visible gangue in the foam layer of the first flotation, and the first collector is used in an amount of 10-80 g / t each time, and the first collector includes one or more of dodecylamine, tetradecylamine, hexadecylamine, octadecylamine, and etheramine.
[0043] In the technical solution of the embodiment of the present application, during the first flotation, the second quartz sand raw material is added into the flotation machine, the pulp concentration, temperature and pH are adjusted, the first collector is added, and the mixture is stirred until the first collector is dispersed; the inflation valve is opened to start inflation, and water is added after inflation for a period of time to make the foam overflow until there is no foam; after repeating several times, the foam layer is observed, and the next stage of operation is entered after no visible gangue is observed by naked eyes in the foam layer. The steps of the second and third flotation are consistent with the first flotation steps.
[0044] In some embodiments, the second flotation is repeated multiple times until there is no visible gangue in the foam layer of the second flotation, and the second collector is used in an amount of 10-80 g / t each time, and the second collector includes one or more of sodium petroleum sulfonate, sodium dodecyl sulfate, and sodium oleate.
[0045] In some embodiments, the third flotation is repeated multiple times until there is no visible gangue in the foam layer of the third flotation, and the third collector is used in an amount of 5-50 g / t each time, and the third collector includes one or more of myristic acid, palmitic acid, rapeseed acid, linoleic acid, and linolenic acid.
[0046] In the technical solution of the embodiment of the present application, the third collector is a fatty acid-based organic surfactant used as a collector, which can remove metal gangue minerals in the ore by combining with metal impurities, usually including metal ores containing copper, zinc, iron, etc., and can make the metal ores hydrophobic by complexing or adsorbing with the metal ions through physical and chemical reactions, thereby being separated and reducing their content in the final high-purity quartz sand product.
[0047] In some embodiments, the drug removal and discharge step in step S4 includes: adding water, gas and stirring to the third flotation tailings to perform drug removal operations, stirring for 30 to 40 minutes, draining, circulating 2 to 3 times, and draining after drug removal is completed.
[0048] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0049] Example 1 S1. Screen the raw materials, use a color sorter for preliminary screening, select the RGB mode, retain only white and transparent particles, set the area threshold to 0.9, remove the raw stones with obvious impurities, and obtain the first quartz sand raw material; S2, crushing the screened first quartz sand raw material through a high pressure roller mill, the roller diameter of the high pressure roller mill is 1000mm, the roller width is 300mm; the motor power is 2×400kW; the feed particle size is ≤30mm, the throughput is 200t / h, the pressure is 10 MPa, and the fine sand is ground into fine sand, sieved and screened, and the fine sand particle size is 60~160 mesh; S3, the magnetic drum speed is set to 40r / min, and two-stage magnetic separation is performed under the condition of a magnetic field strength of 8000Gs to obtain a second quartz sand raw material; S4. Carry out flotation test, adjust the pulp temperature to 35℃ and the concentration to 35%, add HCl to adjust the pH to 2.5, stir for 10 min, and rotate at 500 r / min; add dodecylamine, tetradecylamine and etheramine as the first collector, with the dosage of 80g / t in each stage, and stir for 20 min; open the inflation valve to start inflation, the inflation volume is 1.5m³ / ·min, add water to make the foam overflow after 5 min of inflation, and overflow until there is no foam; repeat 3 stages and carry out the second flotation, adjust the pulp temperature to 35℃ and the pH to 2.5; add sodium dodecyl sulfate and sodium oleate as the second collector, with the dosage of 80g / t in each stage, and stir for 10 min; add water to make the foam overflow after 5 min of inflation, and overflow until there is no foam; repeat 3 stages and carry out drug removal operation, add water and gas and stir, carry out drug removal operation, and stir for 30 After 3 minutes, drain the water, and after 3 cycles, carry out the third flotation, adjust the pulp temperature to 35℃ and pH to 6; add linoleic acid as the third collector, the dosage of each stage is 50g / t, and stir for 10 minutes; after aeration for 5 minutes, add water to make the foam overflow, and overflow until there is no foam, repeat 3 stages and then carry out the de-drug operation.
[0050] S5. Drug removal and discharging: add water and gas to stir, carry out drug removal operation, stir for 40 minutes, drain, recycle 3 times, drain after drug removal, start discharging after drainage, and randomly take samples for ICP testing.
[0051] Example 2 S1. Screen the raw materials, use a color sorter for preliminary screening, select the RGB mode, retain only white and transparent particles, set the area threshold to 0.95, remove the raw stones with obvious impurities, and obtain the first quartz sand raw material; S2, crushing the first quartz sand raw material after screening through a high pressure roller mill, the roller diameter of the high pressure roller mill is 1000mm, the roller width is 300mm; the motor power is 2×400 kW; the feed particle size is ≤30mm; the throughput is 200t / h, the pressure is 15 MPa, and the fine sand is ground into a sieve, and the sieved particle size is 60~160 mesh; S3, the magnetic drum speed is set to 40r / min, and 4-stage magnetic separation is performed under the condition of a magnetic field strength of 6000 Gs to obtain the second quartz sand raw material; S4. Carry out flotation test, adjust the pulp temperature to 40℃, concentration to 40%, add HCl to adjust pH to 2, stir for 15 min, and rotate at 600 r / min; add dodecylamine and tetradecylamine as the first collector, with the dosage of 50g / t in each stage, and stir for 15 min; open the inflation valve, the inflation volume is 1.5m³ / ·min, add water to make the foam overflow after 5 minutes of inflation, and overflow until there is no foam; repeat 5 stages and carry out the second stage operation, adjust the temperature to 40℃ and pH to 2.5; add sodium dodecyl sulfonate and sodium petroleum sulfonate as the second collector, with the dosage of 50g / t in each stage, and stir for 15 min; add water to make the foam overflow after 5 minutes of inflation, and overflow until there is no foam; repeat 5 stages and carry out drug removal operation, add water and gas and stir, carry out drug removal operation, and stir for 30 After 3 minutes, drain the water, and after 3 cycles of drug removal, proceed to the third stage of operation, adjust the temperature to 40℃ and pH to 6; add rapeseed oil acid, linoleic acid, and linolenic acid as collector 3, with a dosage of 30g / t in each stage, and stir for 15 minutes; after aeration for 5 minutes, add water to make the foam overflow, and overflow until there is no foam, repeat 5 stages and then proceed to drug removal operation.
[0052] S5. Drug removal and discharging: Add water, add air and stir to carry out drug removal operation, stir for 30 minutes, drain, and recycle 3 times. Drain after drug removal is completed, and start discharging after drainage. Randomly take samples for ICP testing.
[0053] Example 3 S1. Screen the raw materials, use a color sorter for preliminary screening, select the RGB mode, retain only white and transparent particles, set the area threshold to 1, remove the raw stones with obvious impurities, and obtain the first quartz sand raw material; S2, crushing the screened first quartz sand raw material through a high pressure roller mill, the roller diameter of the high pressure roller mill is 1000mm, the roller width is 300mm; the motor power is 2×400kW; the feed particle size is ≤30mm, the throughput is 200t / h, the pressure is 15 MPa, and the material is ground into fine sand, sieved, and the sieved particle size is 60~160 mesh; S3, the magnetic drum speed is set to 40r / min, and three-stage magnetic separation is performed under the condition of a magnetic field strength of 7000 Gs to obtain the second quartz sand raw material; S4. Carry out flotation test, adjust the temperature to 35℃, concentration to 40%, add HCl and NaOH to adjust pH to 3, stir for 20 min, speed to 400 r / min; add dodecylamine and etheramine as the first collector, the dosage for each stage is 50g / t, stir for 10min; open the inflation valve to start inflation, the inflation volume is 1.5m³ / ·min, add water to make the foam overflow after 5 minutes of inflation, and overflow until there is no foam; repeat 5 stages and carry out the second stage operation, adjust the temperature to 35℃ and pH to 3; add sodium dodecyl sulfate, sodium oleate, and sodium petroleum sulfonate as the second collector, the dosage for each stage is 50g / t, stir for 10 min; add water to make the foam overflow after 5 minutes of inflation, and overflow until there is no foam in the overflow; repeat 5 stages and carry out drug removal operation, add water, gas and stir, carry out drug removal operation, stir for 30 After 3 min, drain the water, and after 3 cycles of drug removal, proceed to the third stage of operation, adjust the temperature to 35℃ and pH to 7; add rapeseed oil acid and linoleic acid as the third collector, with a dosage of 30g / t in each stage, and stir for 10 min; after aeration for 5 min, add water to make the foam overflow, and overflow until there is no foam, repeat 5 stages and then proceed to drug removal operation.
[0054] S5. Drug removal and discharging: Add water, add air and stir to carry out drug removal operation, stir for 30 minutes, drain, and recycle 3 times. Drain after drug removal is completed, and start discharging after drainage. Randomly take samples for ICP testing.
[0055] Comparative Example 1 S1. Crushing. The pegmatite sample is crushed by a jaw crusher. After being crushed into small pieces, it is ground into fine sand by a double-roll mill. The quartz sand after the double-roll mill is sieved to obtain quartz sand with a particle size of 60-160 mesh; the sand making rate is analyzed by screening test.
[0056] S2, the magnetic drum speed is set to 40 r / min, and two-stage magnetic separation is carried out under the condition of magnetic field strength of 8000 Gs; S3. Carry out flotation test, adjust the temperature to 35℃ and the concentration to 35%, add HCl and NaOH to adjust the pH to 2.5, stir for 10min, and rotate at 500 r / min; add 80g / t of the first collector, dodecylamine, tetradecylamine and etheramine, and stir for 20min; open the inflation valve to start inflation, the inflation volume is 1.5 m³ / ·min, add water to make the foam overflow after 5min of inflation, and overflow until there is no foam; repeat 3 stages and carry out the second stage operation, adjust the temperature to 35℃ and pH to 2.5; add 80g / t of sodium dodecyl sulfate and sodium oleate as the second collector, and stir for 10min; add water to make the foam overflow after 5min of inflation, and overflow until there is no foam; repeat 3 stages and carry out the third stage operation, at a temperature of 35℃ and a pH of 6, add 50g / t of linoleic acid as the third collector, and stir for 10min; add water to make the foam overflow after 5min of inflation, and overflow until there is no foam, and repeat 3 stages.
[0057] S4, drug removal and discharging: add water, add air and stir to carry out drug removal operation, stir for 40 minutes, drain, recycle 3 times, drain after drug removal is completed, start discharging after drainage, and randomly take samples for ICP testing.
[0058] S5. After flotation, HF is used as the leaching solution, and the operation is carried out for 9-18 hours at a solid-liquid ratio of 1:1 and a temperature of 60°C. After the acid discharge and deacidification are completed, the material is discharged and random samples are taken for ICP testing.
[0059] Comparative Example 2 S1. Screen the raw materials, use a color sorter for preliminary screening, select the RGB mode, retain only white and transparent particles, set the area threshold to 0.9, remove the raw stones with obvious impurities, and obtain the first quartz sand raw material after color sorting; S2. The first quartz sand raw material after color sorting is crushed by a high pressure roller mill. The roller diameter of the high pressure roller mill is 1000mm, the roller width is 300mm, the motor power is 2×400kW, the feed particle size is ≤30mm, the throughput is 200t / h, the pressure is 10MPa, and the material is ground into fine sand, which is sieved and screened. The particle size of the fine sand is 60~160 meshes. S3, the magnetic drum speed is set to 40 r / min, and two-stage magnetic separation is performed under the condition of magnetic field strength of 8000 Gs; S3. Carry out flotation test, adjust the temperature to 35℃, the concentration to 35%, add HCl and NaOH to adjust the pH to 2.5, stir for 10min, and rotate at 500 r / min; add 80g / t of the first collector, dodecylamine, tetradecylamine and etheramine, and stir for 20min; open the inflation valve to start inflation, the inflation volume is 1.5 m³ / ·min, add water to make the foam overflow after 5min of inflation, and overflow until there is no foam; repeat 3 stages and carry out the second stage operation, adjust the temperature to 35℃ and the pH to 2.5; add 80g / t of the second collector, sodium dodecyl sulfate and sodium oleate, and stir for 10min; add water to make the foam overflow after 5min of inflation, and overflow until there is no foam; repeat 3 stages and carry out drug removal operation.
[0060] S4, drug removal and discharging: add water, add air and stir to carry out drug removal operation, stir for 40 minutes, drain, recycle 3 times, drain after drug removal is completed, start discharging after drainage, and randomly take samples for ICP testing.
[0061] The XRF test results of pegmatite samples are shown in Table 1. The pegmatite samples mainly contain quartz, feldspar, mica and some metal minerals; the main chemical components of quartz are SiO2, the main chemical components of feldspar are SiO2 and Al2O3, and the main chemical components of mica are SiO2 and Al2O3. According to the XRF test results and the estimated chemical composition ratio, the quartz content in the pegmatite used in this case is about 41%, the feldspar content is about 30%, and the mica content is about 29%.
[0062] Table 1 XRF test results of pegmatite samples (%)
[0063] The high-purity quartz sand products prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were subjected to ICP testing. The test results are shown in Table 2.
[0064] Table 2 ICP test results of quartz sand products in implementation cases 1-3 and comparative examples 1-2 (μg / g)
[0065] As can be seen from Table 2, the SiO2 content of the product after color sorting pre-screening is about 94.3456%. Cases 1, 2 and 3 adopt a method of directly preparing 4N8 grade high-purity quartz sand for semiconductor crucibles after flotation proposed in this application under different conditions, and 4N8 grade high-purity quartz sand products can be directly prepared after flotation under fluorine-free and nitrate-free conditions.
[0066] As can be seen from Table 2, compared with the traditional sand making technology in Examples 1 to 3 and Comparative Example 1, the method provided by the present application can obtain a high-purity quartz sand product with a SiO2 content higher than 99.9980% (4N8 grade) after flotation, wherein the SiO2 content of the flotation products obtained in Examples 1, 2, and 3 is 99.9982%, 99.9979%, and 99.9983%, respectively; however, the SiO2 content of the quartz sand product after flotation by the traditional sand making technology is only 99.9953%. In addition, in Comparative Example 1, the quartz sand is further acid-leached after flotation, and the SiO2 content of the quartz sand product is only 99.9979%. It can be seen that the screening of raw materials based on the color sorter can lay a good foundation for subsequent flotation and acid leaching, and the purification effect is better. The experimental data confirm that the method provided by the present invention has fewer steps, can effectively reduce resource waste, and significantly improve efficiency.
[0067] In Comparative Example 1, the SiO2 content of the quartz sand product obtained by adding the third collector increased from 99.9919% (second collector) to 99.9953%, among which the most significant was that the Fe element content decreased from 15.07 μg / g to 4.36 μg / g, the Al element content decreased from 34.80 μg / g to 25.02 μg / g, and the K element content decreased from 10.39 μg / g to 6.39 μg / g, indicating that the addition of the third collector can further remove metal minerals in the product.
[0068] Table 3 describes the sand making rates of different crushing methods in Example 1 and Comparative Example 1. Comparing Example 1 with Comparative Example 1, the high pressure roller mill has higher sand making efficiency. When processing the same weight of pegmatite samples and preparing sand samples with a target particle size of 60-160 mesh, the yield of sand with a qualified particle size obtained by the high pressure roller mill is 85.37%, while the yield of sand with a qualified particle size obtained by the traditional sand making method is only 66.91%.
[0069] Table 3 Sand making rate of traditional sand making method and high pressure roller grinding (%)
[0070] Comparing Example 1 with Comparative Example 2, it can be seen from Table 2 that not using the third collector for flotation purification operation will affect the quality of the floated quartz sand product; the SiO2 content of the floated quartz sand product finally obtained in Comparative Example 2 is 99.9959%. Compared with Example 1, the Fe content in the product is higher, which is 5.83 μg / g, while the Fe content in the product of Example 1 is only 0.24 μg / g, which further proves that the third collector can effectively remove iron-containing metal impurities and further improve product quality.
[0071] Comparative Examples 1 and 2, when only two stages of flotation operations were performed, the SiO2 content of the product obtained in Comparative Example 2 was 99.9959%, and the SiO2 content of the product obtained in Comparative Example 1 was 99.9919%; the difference was that the sand making methods of the two comparative examples were different, Comparative Example 2 used color sorting-high pressure roller mill to selectively crush the raw materials for sand making, and Comparative Example 1 used the traditional sand making method. This result shows that selective crushing and sand making by high pressure roller mill can improve the quality of raw materials in advance and lay a good foundation for subsequent purification operations.
[0072] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A method for preparing 4N8 grade high-purity quartz sand by high-pressure roller mill flotation of pegmatite, characterized in that: The steps include: S1. Color sorting the raw ore to remove the miscellaneous gangue minerals to obtain the first quartz sand raw material; S2, crushing the first quartz sand raw material into fine sand, and then screening and magnetically separating to obtain a second quartz sand raw material; S3, mixing the second quartz sand raw material with water to form a slurry, and then flotation three times in sequence, and obtaining a high-purity quartz sand product after drug removal and material discharge; The step S3 specifically includes the following steps: adding a first collector to the ore pulp for a first flotation to remove mica and obtain a first flotation tailing, wherein the first collector is an amine collector; adding a second collector to the first flotation tailing for a second flotation to remove feldspar and obtain a second flotation tailing, wherein the second collector is an anionic organic surfactant; adding a third collector to the second flotation tailing for a third flotation to remove metal impurity minerals and obtain a third flotation tailing, wherein the third collector is a fatty acid organic surfactant.
2. The method for preparing 4N8 grade high purity quartz sand by high pressure roller mill flotation of pegmatite according to claim 1, characterized in that: In the step S2, the first quartz sand raw material is crushed by a high pressure roller mill, the pressure of the high pressure roller mill is ≤20 MPa, the feed particle size is ≤30 mm, and the throughput is 200-400 t / h.
3. The method for preparing 4N8 grade high purity quartz sand by high pressure roller mill flotation of pegmatite according to claim 1, characterized in that: The particle size of the fine sand is 60-160 meshes.
4. The method for preparing 4N8 grade high purity quartz sand by high pressure roller mill flotation of pegmatite according to claim 1, characterized in that: In step S3, the pulp concentration in the first flotation is 25-45%, the temperature is 35-60°C, and the pH is adjusted to 2-4 by a pH adjuster; the temperature in the second flotation is 35-60°C, and the pH is adjusted to 2-4 by a pH adjuster; the temperature in the third flotation is 35-60°C, and the pH is adjusted to 5-8 by a pH adjuster.
5. The method for preparing 4N8 grade high purity quartz sand by high pressure roller mill flotation of pegmatite according to claim 4, characterized in that: The pH adjuster is one or more of sulfuric acid, hydrochloric acid, nitric acid and sodium hydroxide.
6. The method for preparing 4N8 grade high purity quartz sand by high pressure roller mill flotation of pegmatite according to claim 1, characterized in that: The stirring speed during the flotation process is 200-600 r / min, and the aeration volume is 0.8-1.5 m 3 / min.
7. The method for preparing 4N8 grade high purity quartz sand by high pressure roller mill flotation of pegmatite according to claim 1, characterized in that: The first flotation is repeated for multiple times until there is no visible gangue in the foam layer of the first flotation, and the first collector is used in an amount of 10-80 g / t each time, and the first collector includes one or more of dodecylamine, tetradecylamine, hexadecylamine, octadecylamine, and etheramine.
8. The method for preparing 4N8 grade high purity quartz sand by high pressure roller mill flotation of pegmatite according to claim 1, characterized in that: The second flotation is repeated for multiple times until there is no visible gangue in the foam layer of the second flotation. The second collector is used in an amount of 10-80 g / t each time. The second collector includes one or more of sodium petroleum sulfonate, sodium dodecyl sulfate, and sodium oleate.
9. The method for preparing 4N8 grade high purity quartz sand by high pressure roller mill flotation of pegmatite according to claim 1, characterized in that: The third flotation is repeated for multiple times until there is no visible gangue in the foam layer of the third flotation. The third collector is used in an amount of 5-50 g / t each time. The third collector includes one or more of myristic acid, palmitic acid, rapeseed acid, linoleic acid, and linolenic acid.
10. The method for preparing 4N8 grade high purity quartz sand by high pressure roller mill flotation of pegmatite according to claim 1, characterized in that: The drug removal and discharge step in step S4 includes: adding water, gas and stirring to the third flotation tailings to perform drug removal operation, stirring for 30-40 minutes, draining, circulating 2-3 times, and draining after drug removal is completed.
Citation Information
Patent Citations
Green and efficient method for preparing high-purity quartz
CN116654944A
Magnetite high-pressure roller mill-multi-element tailings pre-discarding and iron and phosphorus recovery system and process
CN118719307A
Ceramic raw material grinding device of high-pressure roller mill
CN221602128U
Comprehensive utilization method of iron ore surrounding rock
CN110142134A
Method for coarse grain separation and dry-type powdering of granite pegmatite
CN110639692A
Cited By
Method for separating and purifying high-purity quartz sand from series of rocks of twinkling, quartz twinkling, granite twinkling and granite
CN120205309A